Innovative bio-inspired solar cells using fly ash-based dye-sensitized cells with fruit extract enhancements and Averrhoa bilimbi electrolyte - Utami, Retyo Wizi Nafa; Dewi, Tresna; Indrayani, Indrayani (SINERGI, 2025)
This study responds to the urgent need for renewable energy in Indonesia, driven by climate change and the energy crisis, by developing dye-sensitized solar cells (DSSCs) using locally sourced, eco-friendly materials. Traditional silicon-based photovoltaic cells, which have plateaued at 27% efficiency, are costly and environmentally unfriendly, leading to the demand for alternatives like DSSCs, which offer lower production costs, flexibility, and effective performance in diffuse light. The research focuses on designing DSSCs with Fe and Mg extracted from fly ash as counter electrodes, dragon fruit peel as a natural dye sensitizer, and Averrhoa bilimbi as an electrolyte booster. UV-Vis spectroscopy demonstrated that dragon fruit dye absorbs light effectively in the 360-700 nm range, peaking at 550 nm, making it an ideal sensitizer for wide-band gap semiconductors. Voltage output tests showed that Fe-doped DSSCs consistently outperformed Mg-doped ones, with Fe-based cells generating a maximum voltage of 413 mV compared to 163 mV for Mg-based cells. Long-term testing over three months further demonstrated Fe-doped cells' superior performance, peaking at 454.6 mV, while Mg-doped cells reached 261.96 mV. These results highlight Fe's effectiveness as a doping material, improving DSSC efficiency and supporting the use of natural dyes and sustainable materials. The study aligns with prior research on the critical role of material properties and solar irradiance in DSSC performance, demonstrating the potential of using fly ash and natural dyes for efficient solar energy solutions in South Sumatra. Future research will focus on optimizing material composition for enhanced performance.